(untitled) (The Lumbini Journal of Business and Economics, 2026)
Purpose: Artificial Intelligence is transforming financial services by enabling automation, personalization, and intelligent decision-making; however, its impact on customer satisfaction in backward regions of Nepal, such as Karnali Province, remains largely unexplored. This study examines how Artificial Intelligence influences customer satisfaction, with Technology-Driven Customer Experience (TDC) serving as a mediating variable. Methods: A descriptive and causal research design is adopted to both describe the current adoption and use of Artificial Intelligence (AI)-enabled financial services and to examine the causal relationships between AI and customer satisfaction. Survey data were collected from 150 respondents who use internet banking, mobile banking, and digital payment services through a structured questionnaire. Construct reliability and validity, as well as the hypothesized relationships, were tested using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results: TDC is significantly positively influenced by digitalization, as shown by the path coefficients (β = 0.749, t = 12.306; β = 0.686, t = 8.487). The findings also reveal a weak but significant direct effect of digitalization on customer satisfaction (β = 0.219, t = 2.891). Furthermore, the model explains 56.1% of the variance in TDC and 74.5% of the variance in customer satisfaction, confirming the mediating role of TDC. Conclusion: Financial institutions should focus on digital skills education, user-centered innovation, and secure platforms to support service adoption and customer satisfaction in semi-urban and rural areas.